'Bare-backing spoils everything. He's spoiled goods': Disposal and disgust, a study of retired power bottom twink Jake Lyons. Issue 1 (2nd January 2016) - Brennan, Joseph
ABSTRACT: This article uses star study and textual analysis of posts on popular gay porn blog TheSword.com as a means to chart the career of retired power bottom twink Jake Lyons and the manner in which his various career and personal decisions – such as to perform bareback and in fetish porn – are critiqued by participants on this blog. I argue that a discourse of disposal and disgust surrounding Lyons and his actions pervade this forum and that this discourse is worthy of scholarly consideration: not only because it relates to sexual health concerns resulting from high-risk sexual practice facing the industry and gay community, but also because it has something to tell us about the consumption of gay porn and the objectification and disposal of gay male performers, twink bottoms particularly.